2013
DOI: 10.4103/0972-124x.107490
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of an early failing implant by guided bone regeneration using resorbable collagen membrane and bioactive glass

Abstract: Implant failure can be divided into early (prior to prosthetic treatment) or late (after prosthetic rehabilitation). Early failure is generally due to interference in the healing process after implant placement. Implants undergoing early failure will show progressive bone loss on radiographs during the healing period (4 to 6 weeks). In the present case report, early progressive bone loss was seen at 6 weeks, after placement of a non-submerged single piece mini implant. Clinical examination revealed peri-implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Conventional protocols for guided bone regeneration (GBR) involve placement of a bone substitute material like hydroxyapatite or b-tricalcium phosphate (b-TCP) at the bone defect site and covering it with a barrier membrane followed by a healing period ranging from 6 to 10 months [1][2][3]. Based on histological findings in animal models, GBR using b-TCP promotes formation of new bone in osseous defect sites as early as 12 weeks [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional protocols for guided bone regeneration (GBR) involve placement of a bone substitute material like hydroxyapatite or b-tricalcium phosphate (b-TCP) at the bone defect site and covering it with a barrier membrane followed by a healing period ranging from 6 to 10 months [1][2][3]. Based on histological findings in animal models, GBR using b-TCP promotes formation of new bone in osseous defect sites as early as 12 weeks [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The permittivity was calculated using Equation (2). [30][31][32][33] where C p and R p represent the measured capacitance and resistance, d is the sample thickness, A the electrode area and ɛ 0 the permittivity of the empty space (8.8542 × 10 −12 F/m).…”
Section: Structural and Morphological Characterizationmentioning
confidence: 99%
“…Marchetti et al 65) described this area of attachment as "a biological seal", since it isolates the oral cavity from bone and hence greatly affects the success of dental implants. Related to oral implants, peri-implantitis has been discussed extensively 34) . B-G has shown to be active against supra-and sub-gingival bacteria 9) , further underlining its potential benefits as part of an implanted device by means of metal surface coating.…”
Section: Metal Surface Biofunctionalization: Coating Materials For Denmentioning
confidence: 99%
“…There has been a number of clinical studies that have demonstrated consistent results in a variety of alternative treatments including the surgical modification/reduction (elevation) of the maxillary sinus 30) , the regeneration of interproximal bone defects in periodontal therapies 31) , periapical application during endodontic microsurgery 32) (Fig. 3), management of cystic defects 33) , as well as reconstructive procedures for treating peri-implantitis 34) . All these clinical applications have one thing in common -the proven efficacy and effectiveness to bond with hard tissue and enhance its growth due to the osteoconductive and osteostimulatory properties of the glass.…”
Section: Clinical Applicationsmentioning
confidence: 99%